Implementation of the construct of motor competence into physical education at primary schools with the apre-model - Holzweg, M. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction In the times of urbanisation, television and new media it becomes more and more important to guarantee a normal motor development of the children. Without objective and standardized motor test there is no chance to measure the level of motor competence of children. It seem, that that with the development of an appropriate motor test and the cooperation of physical education teachers and parents a normal motor development achieved. Methods The used research method is correlative. The data base consists of 600 german and of 225 southafrican Primary School children. The technique of data collection was the Motor Competence Test. The technique of data analysis was empirical-oriented (quantitative). Test norms were developed and mean comparisons were done with SPSS. Results The Motor Competence Test (13 items) was developed. Test data of 600 german and of 225 southafrican Primary School children are available. Programmes to improve the Motor Competence of Primary School children were also developed. Norms and a computer-based version of the Motor Competence Test are available as well. Discussion/ Conclusions Within this project of the development of the Motor Competence Test and Programmes to improve the motor competence of Primary School children it became obvious, that the construct of motor competence can be implemented in Physical Education at Primary Schools. The Motor Competence Test should now be contributed to more Primary Schools in order to guarantee a normal motor development of Primary School children.